Hyper-Aerotolerant Campylobacter coli from Duck Sources and Its Potential Threat to Public Health: Virulence, Antimicrobial Resistance, and Genetic Relatedness - Guk, Jae-Ho (Microorganisms, 2019)
Campylobacter, a common foodborne human pathogen, is considered sensitive to oxygen. Recently, aerotolerant (AT) Campylobacter jejuni with the ability to survive under aerobic stress has been reported. Here, we investigated the prevalence of hyper-aerotolerant (HAT) Campylobacter coli from duck sources (118 carcasses and meat) and its characteristics to assess potential impacts on public health. Half of 56 C. coli isolates were HAT and most harbored various virulence genes including flaA, cadF, cdtA, ceuB, and wlaN. Moreover, 98.2% of C. coli isolates showed resistance to quinolones, including ciprofloxacin (CIP), and nine (16.1%) showed high-level resistance to ciprofloxacin (Minimum Inhibitory Concentration, MIC ≥ 32 μg/mL) and most of these were HAT. Based on genetic relatedness between C. coli from duck sources and those from human sources (PubMLST and NCBI), HAT isolates sharing the same MLST sequence types were significantly more prevalent than those not sharing the same sequence types as those from human sources. Therefore, HAT C. coli is prevalent in duck sources, and is most likely transmitted to humans through the food chain given its aerotolerance. This being so, it might pose a threat to public health given its virulence and antimicrobial resistance (AMR). This study will assist in improving control strategies to reduce farm-to-table HAT C. coli transmission to humans.